OBTENÇÃO E CARACTERIZAÇÃO DO SISTEMA CoxFe2-xO4 - Zielasco, Kátia (2007)
This work investigated the influence of Co dopant on the CoxFe2O4 system micro structural properties. The Co concentrations used varied in 0, 8, 16, 24 and 32 mol at the hematite phase. Samples were prepared from the Pechini citrate solution organic route, thermally treated at 580 and 750C for an hour and thirty minutes and sintered at 1000C for two hours. The Co doped samples presented, besides the trigonal hematite, the maghemite spinel phase. Besides, the unitary cell volume in this phase increases with the addition of dopant, which does not occur in the hematite phase, characterizing that the Co ion is probably only entering the crystalline reticulum of the maghemite phase, once there is no additional phase containing this ion. This analysis was carried out using Xray diffraction data through the powder and Rietveld Methods. The characterization by scanning electronic microscopy confirmed that homogeneous samples were obtained, proving the suitability of the Pechini Method for this purpose. Electrical characterization was possible only for the pure sample, which presented NTC behaviour (negative temperature coefficient), NTC curves were not observed for the doped samples in the conditions analyzed.